Research on the Dynamic Mechanical Properties and Constitutive Models of Steel Fiber Reinforced Concrete and Polypropylene Fiber Reinforced Concrete - Jie Huang; Yi Zhang; Yubin Tian; Hengheng Xiao; Jun Shi; Jiyang Shen; Nianlin Zhang (Advances in Civil Engineering)
This paper presents the results of an experimental research designed to investigate the dynamic mechanical properties and constitutive model of fiber reinforced concrete (FRC), including steel fiber reinforced concrete (SFRC) and polypropylene fiber reinforced concrete (PFRC) under fast loading. Experimental results are achieved by using the electrohydraulic servo loading test method, implying that the dynamic mechanical properties of PFRC and SFRC, such as peak stress, peak strain, and toughness, are positively affected by strain rate. The experimental elastic modulus test results of FRC with different fiber contents indicate that the elastic modulus is positively affected by polypropylene or steel fibers and increases with the increment of fiber content. Finally, the experimental stress-strain curves obtained in the MTS electrohydraulic servo system test are fitted by a damage dynamic constitutive model of FRC. The good fitting with experimental results proves that the model could be appropriate to describe the dynamic mechanical properties of FRC.